The Impact Of Parental Verbal Violence On Children's Learning Interest At Ra Al-Hidayah In The 2024-2025 Academic Year - Aini, Finatul; Ramzi, Muhajirin; Sumiadi, Raden (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Abstract. The purpose of this study is to know and understand how the forms of verbal violence commited by parents against children and the conditions of children’s interest in learning at RA Al-hidayah the research method used is a qualitative approach and the type of case study research with the Milles and Hubbermen research model and uses data collection techniques in the from of observation interviews documentation. Based on the results of research and observations carried out at RA Al-hidayah school, it is still found that some parents commit violence against children, one of which is verbal violence as for the forms of verbal violence experienced by children at RA Al-hidayah scool, such as hars words, scolding and giving threats to children the condition of childre’s interest in learning at RA Al-hidayah is that is has a positive and negative impact on children, from the total number of 34 students, 8,5% were found to have a negative impact of verbal violence by parents and verbal violence obtained from the school environment, while 15% were found to have a positive and negative impact on childrent. Kaywods: Verbal Abuse, Learning Interst